Scar Satisfaction Post Thyroidectomy and its Impact on Quality of Life - Aamir Yousuf; Ankit Gairola; Salman Khurshid; Sajad Majid Qazi (Journal of Head & Neck Physicians and Surgeons, 2025)
Background: Visible neck scars following thyroidectomy can affect patients’ psychosocial well-being. This study aimed to assess postoperative scar satisfaction and its correlation with quality of life (QoL) using validated tools. Materials and Methods: A prospective observational study was conducted on 50 patients undergoing thyroidectomy for differentiated thyroid carcinoma. Scar assessment was done at 3–6 months postsurgery using the patient and observer scar assessment scale and the patient scar assessment questionnaire. Quality of life was evaluated using the EORTC QLQ–THY34 questionnaire. Data were analyzed to determine the association between scar satisfaction and QoL. Results: Most patients reported moderate satisfaction with their scars. Female patients and younger individuals were more likely to report dissatisfaction. A significant correlation was found between low scar satisfaction scores and poorer QoL, particularly in domains of social and emotional functioning. Scar characteristics such as length and hypertrophy had a greater impact on satisfaction than suture type. Conclusion: Postthyroidectomy scar appearance significantly affects patient QoL. Attention to cosmetic outcomes and patient counseling are essential components of thyroid cancer management.